The Pattern of the structure of the event in the novel "Fihres" by Sinan Anton - Dardas, Rawan Ahmad Zakaria; Alhashemi, Badeeah Khaleel Ahmed (Al-Adab Journal, 2022)
The events are the main element and backbone of all the artistic elements in any novel, as their threads intertwine according to the logic of the duality of the cause and effect, and therefore they are the main engine of the body of the tale. Each novel differs from the other in the way events are structured and distributed according to a specific pattern that gives it its own system, and a single novel may mix more than one pattern in its construction. Critics, led by the Russian Formalists, have been concerned with classifying the formats on which the events of the novel are based, and they have concluded - after analyzing a number of narrative texts - to several formats, including: the sequential pattern, the circular pattern, the implied pattern, the parallel pattern, and others. A number of writers of the new Arabic novel have been influenced by modern structural patterns, such as: the rotation and circular patterns, among them the Iraqi novelist and poet Sinan Antoun. This study seeks to shed light on the patterns of the structure of the event in his novel: “Fihres”, taking advantage of the data of the structural method. It begins with an introduction in which we explain the concept of structure, in language and convention, with an explanation of its prominent characteristics and features. Then it studies the patterns of the event structure in the novel through three axes. The first section: the event structure, and the second section: the structuring of the event. And the third section: the plot of the novel. The study concluded with results, including: that the events in the novel “Fihres” alternate according to three patterns, namely: the alternation pattern, the succession pattern, and the circular pattern, with the predominance of the rotation pattern, which is present from the beginning of the novel and continues until its end, forming the solid template that is built on the story.